2023
DOI: 10.3390/ph16081183
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In Silico Logp Study, and In Vivo Analgesic Activity of Analogs of Tetrapeptide FELL

Boryana Borisova,
Hristina Nocheva,
Stéphane Gérard
et al.

Abstract: Background: The inflammatory process represents a specific response of the organism’s immune system. More often, it is related to the rising pain in the affected area. Independently of its origin, pain represents a complex and multidimensional acute or chronic subjective unpleasant perception. Currently, medical doctors prescribe various analgesics for pain treatment, but unfortunately, many of them have adverse effects or are not strong enough to suppress the pain. Thus, the search for new pain-relieving medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Parent compound FELL (Phe-Glu-Leu-Leu-OH) and four analogs of the tetrapeptide were previously evaluated in vivo for their analgesic activity [44]. The performed experiments showed that Leu is the best choice as hydrophobic amino acid in positions 3 and 4 of the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Parent compound FELL (Phe-Glu-Leu-Leu-OH) and four analogs of the tetrapeptide were previously evaluated in vivo for their analgesic activity [44]. The performed experiments showed that Leu is the best choice as hydrophobic amino acid in positions 3 and 4 of the sequence.…”
Section: Discussionmentioning
confidence: 99%